2022
DOI: 10.1039/d2ta02463b
|View full text |Cite
|
Sign up to set email alerts
|

Supported Cu3 clusters on graphitic carbon nitride as an efficient catalyst for CO electroreduction to propene

Abstract: The electroreduction of carbon monoxide (COER) to multi-carbon (C2+) products has been emerging as a promising strategy for generating value-added fuels and chemicals, yet the development of efficient catalyst for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 70 publications
(88 reference statements)
0
10
0
Order By: Relevance
“…Remarkably, both of the C atoms in the formed CH 2 CO* species are bound with the C active sites in the CuC 5 catalyst with a length of about 1.53 Å. Thermodynamically, this kind of C–C coupling is an exothermic process with a Δ G value of −0.93 eV, which is more negative than that of the further hydrogenation of CH 2 * to CH 3 * (Δ G = −0.60 eV) during the formation of the CH 4 product, indicating the great promises for the CH 2 CO* formation. Furthermore, this reaction of CH 2 * + CO → CH 2 CO* only requires an ultralow kinetic barrier of 0.35 eV (Figure S8), which is lower than those of some previously reported catalysts, such as boron nitride nanoribbons (1.30 eV) and anchored Cu clusters (0.43 eV) . Overall, the obtained CH 2 * species can effectively couple with CO to generate the vital CH 2 CO* intermediate from the structural, thermodynamic, and kinetic perspectives, which normally helps trigger the subsequent formation of multicarbon products.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Remarkably, both of the C atoms in the formed CH 2 CO* species are bound with the C active sites in the CuC 5 catalyst with a length of about 1.53 Å. Thermodynamically, this kind of C–C coupling is an exothermic process with a Δ G value of −0.93 eV, which is more negative than that of the further hydrogenation of CH 2 * to CH 3 * (Δ G = −0.60 eV) during the formation of the CH 4 product, indicating the great promises for the CH 2 CO* formation. Furthermore, this reaction of CH 2 * + CO → CH 2 CO* only requires an ultralow kinetic barrier of 0.35 eV (Figure S8), which is lower than those of some previously reported catalysts, such as boron nitride nanoribbons (1.30 eV) and anchored Cu clusters (0.43 eV) . Overall, the obtained CH 2 * species can effectively couple with CO to generate the vital CH 2 CO* intermediate from the structural, thermodynamic, and kinetic perspectives, which normally helps trigger the subsequent formation of multicarbon products.…”
Section: Resultsmentioning
confidence: 74%
“…Starting from the activated CO* species, where * represents the adsorption site, we found that this intermediate prefers to be reduced to CHO*, which is located on the C site of S8), which is lower than those of some previously reported catalysts, such as boron nitride nanoribbons (1.30 eV) 59 and anchored Cu clusters (0.43 eV). 60 Overall, the obtained CH 2 * species can effectively couple with CO to generate the vital CH 2 CO* intermediate from the structural, thermodynamic, and kinetic perspectives, which normally helps trigger the subsequent formation of multicarbon products.…”
Section: Ecor Catalytic Performance After Confirming the Basic Struct...mentioning
confidence: 98%
“…They are lower than those of recently reported catalysts, such as the Cu(111) surface (−0.97 V), 52 cobalt porphyrin (−0.56 V), 53 nonmetallic N-doped graphene (−0.58 V), 54 and Cu 3 @g-C 3 N 4 (−0.45 V). 49 As shown in Fig. S5, † aer the generation of *CHO, the hydrogenation process at the O site or C site can form two different intermediates, that is, with the C atom attached to the *CHOH at the B active site or the *OCH 2 anchored by the O atom.…”
Section: Co Electrocatalytic Reactionmentioning
confidence: 99%
“… 21 25 This strategy also resolves the feedstock utilization and stability problems caused by carbonate formation in the CO 2 electrolyte. 26 , 27 Nevertheless, further innovation of CO (2) R electrocatalysts with more mechanistic insights is greatly demanded.…”
Section: Introductionmentioning
confidence: 99%
“…The modern economy has witnessed massive consumption of fossil resources, causing a severe energy crisis and a warming climate. The electrolysis of CO 2 emerges as a promising technology for reducing CO 2 emission because it facilitates CO 2 fixation in a clean, facile manner while producing fuels. Depending on the catalyst utilized, waste CO 2 can be converted into CO, CH 4 , C 2 H 4 , EtOH, etc. At present, CO 2 reduction (CO 2 R) to two-electron (2e) products (i.e., CO and formate) has been well developed, and producing CO in this way is being commercially deployed. By contrast, generating value-added deep reduction products is mainly achieved on Cu-based catalysts while remaining less efficient. To facilitate the multi-electron CO 2 R process, much work has been conducted on the reaction mechanisms, raising an important consensus that *CO is a key intermediate. Accordingly, one strategy is to skip the sluggish CO 2 activation and implement CO reduction (COR), which has exhibited improved efficiency for generating multi-electron products. This strategy also resolves the feedstock utilization and stability problems caused by carbonate formation in the CO 2 electrolyte. , Nevertheless, further innovation of CO (2) R electrocatalysts with more mechanistic insights is greatly demanded.…”
Section: Introductionmentioning
confidence: 99%